2006
DOI: 10.1107/s1600536806026043
|View full text |Cite
|
Sign up to set email alerts
|

Methyltrans-6-oxo-11-thiophen-2-yl-11,12-dihydro-6H-dibenzo[c,h]chromene-12-carboxylate

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean (C-C) = 0.009 Å Disorder in main residue R factor = 0.084 wR factor = 0.254 Data-to-parameter ratio = 12.5For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The proposed trans configuration was further confirmed independently by X‐ray diffraction analysis of 5a (Figure 1, left; for details see the Supporting Information). The data is in agreement with a previously reported X‐ray study of the methyl ester of 5h ,9f which showed that it is a conformationally rigid compound. Furthermore, the observed 3 J 11,12 coupling constant of 1.2 Hz did not depend on the polarity of the solvent used for recording the NMR spectra, in contrast to the conformationally more flexible 3,4‐disubstituted 3,4‐dihydroisocoumarin 9g.…”
Section: Resultssupporting
confidence: 92%
“…The proposed trans configuration was further confirmed independently by X‐ray diffraction analysis of 5a (Figure 1, left; for details see the Supporting Information). The data is in agreement with a previously reported X‐ray study of the methyl ester of 5h ,9f which showed that it is a conformationally rigid compound. Furthermore, the observed 3 J 11,12 coupling constant of 1.2 Hz did not depend on the polarity of the solvent used for recording the NMR spectra, in contrast to the conformationally more flexible 3,4‐disubstituted 3,4‐dihydroisocoumarin 9g.…”
Section: Resultssupporting
confidence: 92%